Дослідження потенційних можливостей технології lorawan в умовах міської забудови - Слободюк, В. М. (ХНУРЕ, 2019)
This article describes principle of operation and main technical characteristics of modern open energy-efficient network protocol LoRaWAN. The LoRaWAN provides significant advantages over Wi-Fi and cellular networks due to the ability to deploy inter-machine (M2M) communications.